The grabarisms in Sayat-Nova’s poems - Torabi, Maryam (Bulletin of Yerevan University B: Philology, 2021)
Sayat-Nova, an eighteenth-century Armenian ashugh and poet, who wrote poems in Tiflis dialect, in his compositions used the Classical Armenian language elements. This paper is considered to the linguistic analyze of these elements, which are called grabarisms. The Classical Armenian forms of Sayat-Nova’s poetry are discussed in three groups: 1․phonetic, 2․lexical-grammatical, 3․syntactic. The lexico-grammatical units of Classical Armenian are most widely used in the poetry of Sayat-Nova, which give originality to the language of Sayat-Nova’s poetry and they are one of its peculiarities.